2019
DOI: 10.3390/f11010040
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Changes Associated with Land Use Type in the Forest Montane Region of Northeast China

Abstract: Soil microorganisms play a vital role in the biogeochemical cycle, whereas land use change is one of the primary factors that affects the biodiversity and functionality of terrestrial ecosystems. The composition and diversity of bacterial communities (by high-throughput sequencing of the bacterial 16S rRNA gene) were evaluated in the soils of the Montane Region of Northeast China, across different land use types, e.g., natural secondary forest (Quercus mongolica, QM), shrubland (SL), coniferous plantation (Lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
(61 reference statements)
2
12
1
Order By: Relevance
“…However, the Gemmatimonadota population remarkably decreased after afforestation, although abundant nutrients (e.g., higher carbon) were found in afforested soils than in CL ( Figure 2 ). This finding is consistent with the study conducted by Wu et al (2019) , who reported the higher relative abundance of Gemmatimonadota in agricultural soil than that in natural secondary forest, coniferous plantation, and shrubland. The members of Gemmatimonadota are aerobes, that are widely distributed in agricultural soils ( Li et al, 2020 ; Sun et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, the Gemmatimonadota population remarkably decreased after afforestation, although abundant nutrients (e.g., higher carbon) were found in afforested soils than in CL ( Figure 2 ). This finding is consistent with the study conducted by Wu et al (2019) , who reported the higher relative abundance of Gemmatimonadota in agricultural soil than that in natural secondary forest, coniferous plantation, and shrubland. The members of Gemmatimonadota are aerobes, that are widely distributed in agricultural soils ( Li et al, 2020 ; Sun et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Proteobacteria and Acidobacteria were also found to be the most abundant phyla in a temperate deciduous broadleaved forest and a tropical mountain rainforest in China [ 46 ]. High abundance of Proteobacteria, Actinobacteria, Acidobacteria, Chloroflexi, Gemmatimonadetes, Verrucomicrobia, Bacteroidetes, Planctomycetes, Saccharibacteria and Nitrospirae was found in agricultural and forest soils from China [ 47 ]. Proteobacteria and Firmicutes are considered as copiotrophic microbes dominating soils with higher carbon availability with a higher net carbon mineralization rate, whereas Acidobacteria and Chloroflexi, as well as Verrumicrobia and Gemmatimonadetes (also present in our samples), are oligotrophic microbes [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of native forests to plantations alters the diversity and functioning of forest ecosystems. Land use practices that can diminish land degradation garner enormous attention globally ( 4 6 ). A keen understanding of the influence of land conversion from native forests to plantations on bacterial communities that control key biogeochemical processes is significant for environmental sustainability.…”
Section: Announcementmentioning
confidence: 99%